Impurity transport driven by fishbones in MAST. (6th February 2015) - Cecconello, M.; Jones, O.M.; Garzotti, L.; McClements, K.G.; Carr, M.; Henderson, S.S.; Sharapov, S.E.; Klimek, I.
Abstract: In MAST, bursting toroidal Alfvén eigenmodes and fishbones are observed to give rise to an asymmetric perturbation to the soft x-ray (SXR) emission close to the magnetic axis which grows and decays on the time scale of the fishbone evolution. As the fishbone nears its maximum amplitude, the SXR emission starts to increase (decrease) at radial positions smaller (larger) than the radial position of the magnetic axis. This trend in the SXR emission persists for a few milliseconds, until the fishbone starts to decay in amplitude and the slower overall trend of the SXR emission once again becomes dominant. A preliminary analysis suggests that the change in the SXR emission is due to the localized accumulation of high- Z impurities, sustained against parallel transport by the effects of fishbones on the fast ion population.